Cell-lineage specificity of primary cilia during postnatal epididymal development. Issue 10 (18th September 2018) - Bernet, Agathe; Bastien, Alexandre; Soulet, Denis; Jerczynski, Olivia; Roy, Christian; Bianchi Rodrigues Alves, Maira; Lecours, Cynthia; Tremblay, Marie-Ève; Bailey, Janice L; Robert, Claude; Belleannée, Clémence
Abstract: STUDY QUESTION: Where are primary cilia (PC) organelles located during postnatal epididymal development? SUMMARY ANSWER: Our findings unveil the existence of PC sensory organelles in different epididymal cell types according to postnatal development stage. WHAT IS KNOWN ALREADY: Primary cilia are sensory organelles that orchestrate major signaling pathways during organ development and homeostasis. Epididymal PC have been detected in the horses, donkey and mules but their cell-lineage specificity has never been investigated in this organ. STUDY DESIGN, SIZE, DURATION: A longitudinal study was performed by examining tissue from n = 3 to n = 10 transgenic mice at different times of postnatal development. Tissues were fixed by intracardiac perfusion and the epididymides collected. PARTICIPANTS/MATERIALS, SETTING, METHODS: Transmission electron microscopy and confocal microscopy/3D reconstruction were used on a double transgenic mouse model expressing endogenous fluorescence in PC and centrioles (Arl13b-mCherry/Centrin2-GFP). Several PC parameters (i.e. length, orientation relative to the lumen) were quantified by using an image-processing pipeline. Epididymal tissues and serum-free cultures of DC2 immortalized epididymal principal murine cell lines were used to identify primary ciliary signaling components. MAIN RESULTS AND THE ROLE OF CHANCE: We report here a constitutive localization of PC in peritubular myoid cells and a dynamic profiling in epithelial cells throughout postnatal epididymal development. While PC are present at the apical pole of the undifferentiated epithelial cells from birth to puberty, they are absent from the apical pole of the epithelium in adults, where they appear exclusively associated with cytokeratin 5-positive basal cells. We determined that PC from epididymal cells are associated with polycystin 1 (PC1), polycystin 2 (PC2), and Gli-3 Hedgehog signaling transcription factor. No inter-individual variability was observed within each age group. LIMITATIONS, REASONS FOR CAUTION: As our present study is descriptive and performed exclusively in the mouse, future functional studies will be required to unravel the contribution of these organelles in the control of reproductive functions. WIDER IMPLICATIONS OF THE FINDINGS: Acknowledging the important roles played by PC sensory organelles in organ homeostasis and development in humans, our work opens new avenues of research concerning the cellular control of epididymal functions, which are essential to male fertility. STUDY FUNDING/COMPETING INTEREST(S): Study funded by an NSERC operating grant to CB (RGPIN-2015–109194). No competing interest to declare.